Kendala Sertifikasi Halal Pada UMKM di Indoneisa: Sebuah Kajian Literatur - Salihah Khairawati; Murtiyani, Siti; Wijiharta, Wijiharta; Yusanto, Ismail; Murtadlo, Mu’tashim Billah (Cattleya Darmaya Fortuna, 2025)
This study examines the obstacles faced by MSMEs in Indonesia related to the implementation of the halal certification program which is a mandate of the Halal Product Guarantee Law (UUJPH). A review of the literature which is the result of empirical research and literature manuscript research was conducted with the assistance of Perish or publish on articles published from 2015 to 2023 with the keyword problems or challenges of halal certification in Indonesia. The next stage of selecting relevant articles was selected for analysis and drawing conclusions. The results of the study found that there are three main obstacles faced by MSMEs in implementing the halal certification program, internal obstacles, namely the lack of halal product literacy, limited resources, both human resources and financial resources, low technology, low awareness of MSME actors towards halal products. External obstacles include the high cost of halal product certification, a complicated and digital-based certification process and lack of support from related institutions, limited access to facilities such as laboratories and lack of socialization of legal regulations and laws on halal products.